Penerapan Restoratif Justice Dalam Penanganan Konflik Di Masyarakat - Agni Wisnu Brata; Amin Purnawan; Ira Aulia (Jurnal Hukum Khaira Ummah, 2020)
Solving problems or conflicts in criminal cases, not necessarily solved through legal channels or through courts. So far, in the process of lawsuit as stipulated in the Criminal Procedure Code, the interest of the victim does not get attention, so that what the victim and the family want can not be fulfilled. The imposition of criminal judgment, not effective because it has not been able to provide deterrent effect for the perpetrator. In addition, the victim's losses are not compensated. Therefore, the settlement of criminal cases by applying restorative justice will be able to provide solutions for the handling of conflicts in the community, involving the perpetrators, victims, communities, and law enfor-cement.Keywords : Restorative Justice, Conflict, and Society